Addition of Flucytosine to Fluconazole for the Treatment of Cryptococcal Meningitis in Africa: A Multicountry Cost-effectiveness Analysis. (28th February 2019) - Shiri, Tinevimbo; Loyse, Angela; Mwenge, Lawrence; Chen, Tao; Lakhi, Shabir; Chanda, Duncan; Mwaba, Peter; Molloy, Síle F; Heyderman, Robert S; Kanyama, Cecilia; Hosseinipour, Mina C; Kouanfack, Charles; et al.
Abstract: Background: Mortality from cryptococcal meningitis remains very high in Africa. In the Advancing Cryptococcal Meningitis Treatment for Africa (ACTA) trial, 2 weeks of fluconazole (FLU) plus flucytosine (5FC) was as effective and less costly than 2 weeks of amphotericin-based regimens. However, many African settings treat with FLU monotherapy, and the cost-effectiveness of adding 5FC to FLU is uncertain. Methods: The effectiveness and costs of FLU+5FC were taken from ACTA, which included a costing analysis at the Zambian site. The effectiveness of FLU was derived from cohorts of consecutively enrolled patients, managed in respects other than drug therapy, as were participants in ACTA. FLU costs were derived from costs of FLU+5FC in ACTA, by subtracting 5FC drug and monitoring costs. The cost-effectiveness of FLU+5FC vs FLU alone was measured as the incremental cost-effectiveness ratio (ICER). A probabilistic sensitivity analysis assessed uncertainties and a bivariate deterministic sensitivity analysis examined the impact of varying mortality and 5FC drug costs on the ICER. Results: The mean costs per patient were US 847 (95% confidence interval [CI] 776–927) for FLU+5FC, and US 628 (95% CI 557–709) for FLU. The 10-week mortality rate was 35.1% (95% CI 28.9–41.7%) with FLU+5FC and 53.8% (95% CI 43.1–64.1%) with FLU. At the current 5FC price of US 1.30 per 500 mg tablet, the ICER of 5FC+FLU versus FLU alone was US 65 (95% CI 28–208) per life-year saved. Reducing the 5FC cost to between US 0.80 and US 0.40 per 500 mg resulted in an ICER between US 44 and US 28 per life-year saved. Conclusions: The addition of 5FC to FLU is cost-effective for cryptococcal meningitis treatment in Africa and, if made available widely, could substantially reduce mortality rates among human immunodeficiency virus–infected persons in Africa. Abstract : The combination of flucytosine plus fluconazole (FLU) is cost-effective, compared with the commonly used regimen of FLU monotherapy, for cryptococcal meningitis treatment in Africa, with an incremental cost-effectiveness ratio of US 65 per life-year saved at the current price.